13. CHARACTERISTICS OF THE OPTIC NERVE SHEATH DIAMETER MEASURED BY ULTRASOUND IN CHILDREN WITH SUSPECTED INCREASED INTRACRANIAL PRESSURE (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the characteristics of optic nerve sheath diameter (ONSD) measured by ultrasound in children with suspected increased intracranial pressure (ICP).Materials and methods: A descriptive cross-sectional study at the pediatric intensive care unit (PICU), Children's Hospital 2 between February and August 2024 on 142 children, including 2 groups: suspected increased ICP (n=69) and without increased ICP (n=73).Results: The ONSD values ​​measured on PICU admission (right eye, left eye and the average of both eyes) between the two groups had a significant difference with P < 0.05. Applying the ROC curve to analyze the average ONSD value in four age groups (10) recorded AUROC > 0.9, showing good accuracy of ONSD in assessing raised ICP. The suggested cut-off values ​​for diagnosing increased ICP in the four age groups were: 4.2 mm; 4.8 mm; 5.0 mm and 5.3 mm, respectively. There was a negative correlation between the average ONSD value of both eyes and GCS  at the time of ICU admission, ICU discharge and during the first 3 days with the treatment of cerebral edema. The final and highest mean ONSD values ​​during follow-up were associated with mortality.Conclusions: Ultrasound measurement of the optic nerve sheath diameter is a useful tool in the evaluation of increased intracranial pressure among PICU-admitted pediatric patients.
Keywords: ultrasound-based ONSD, increased ICP in children.